Assessment of Female Patients Burden undergoing Hemodialysis at Shar Teaching Hospital in Sulaymaniyah City - Kalthum Mohammed Gharib Mohammed; Mahabat Hassan Saeed; Sanaa Othman Karim; Nazera Salam Mena; Khelan Akram Mohammed (UHD Journal of Science and Technology)
Background: Hemodialysis patients with chronic kidney failure end-stage renal disease (ESRD) will encounter various pressures, functional limitations, dietary restrictions, pharmaceutical side effects, workplace challenges, as well as social and dynamic changes. Health problems and a lower quality of life, in general, can arise from the roles that gender stereotypes and sex discrimination impose. Within this research, we sought to determine the burden of female hemodialysis patients in Sulaymaniyah City and to examine the impact of several sociodemographic parameters on this burden. Materials and Methods: A cross-sectional quantitative design, a convenient selection of 53 female patients with ESRD receiving hemodialysis was comprised. The study was carried out at the Shar Teaching Hospital’s dialysis department in Sulaymaniyah City. Results: The study participants’ mean age was determined to be 55.8 ± 14.6 years, with the majority (41.0%), falling between the age range of 41 and 80 years. 100% of the research sample reported feeling fatigued. The results indicate that there were significant associations found between age groups (P = 0.030), level of education, marital status, and the assessment of female patients’ burden of undergoing hemodialysis. The majority of participants (41.5%) had low assessments of female patients’ burden. Conclusion: Most of the instances involved illiterate housewives who had been on hemodialysis for longer than 10 years. Most research samples exhibited lower energy levels, and almost all patients complained of being fatigued. The assessment of the burden of female patients receiving hemodialysis showed positive correlations with age groups, educational attainment, and marital status. Otherwise, no correlation was observed between the patients’ work, place of residence, length of hemodialysis treatment, and the overall estimate of the burden experienced by female patients.